A description of the knowledge and attitudes towards bystander CPR amongst participants in a community outreach initiative in Cape Town - Zaayman, Heinri (Stellenbosch : Stellenbosch University, 2020)
Thesis (MFamMed)--Stellenbosch University, 2020.